1989
DOI: 10.1037/0022-3514.56.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Circular reasoning about interpersonal behavior: Evidence concerning some untested assumptions underlying diagnostic classification.

Abstract: There are a number of strong geometric and substantive assumptions involved when assessment instruments are used to classify persons into typological categories denned by the coordinates of the Interpersonal Circle. These assumptions were derived from interpersonal theory and stated in the form of hypotheses that were tested with reference to the revised Interpersonal Adjective Scales (IAS-R) in three groups of university undergraduates. Study 1 found strong support for the geometric and psychometric assumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
264
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(282 citation statements)
references
References 21 publications
(22 reference statements)
13
264
1
4
Order By: Relevance
“…This 2D structure of face evaluation is consistent with well established dimensional models of social perception (19,22,23). For example, Wiggins et al (19,23), starting with a large set of traits describing interpersonal relationships, have shown that interpersonal perception can be described by two orthogonal dimensions, affiliation and dominance, that are similar to the dimensions identified here.Judgments of trustworthiness were closest in space to the first PC, and judgments of dominance were closest to the second PC ( Fig. S2 and Table S3).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…This 2D structure of face evaluation is consistent with well established dimensional models of social perception (19,22,23). For example, Wiggins et al (19,23), starting with a large set of traits describing interpersonal relationships, have shown that interpersonal perception can be described by two orthogonal dimensions, affiliation and dominance, that are similar to the dimensions identified here.Judgments of trustworthiness were closest in space to the first PC, and judgments of dominance were closest to the second PC ( Fig. S2 and Table S3).…”
supporting
confidence: 51%
“…Judgments of dominance, aggressiveness, and confidence had the highest loading on the second PC, suggesting that it can be interpreted as dominance evaluation (19). This 2D structure of face evaluation is consistent with well established dimensional models of social perception (19,22,23). For example, Wiggins et al (19,23), starting with a large set of traits describing interpersonal relationships, have shown that interpersonal perception can be described by two orthogonal dimensions, affiliation and dominance, that are similar to the dimensions identified here.…”
supporting
confidence: 51%
“…Interestingly, on the semantic-conceptual level, the 2D model of Oosterhof & Todorov (2008), which was built on face-based person evaluation, fits other two dimensional models of social perception, such as the Stereotype Content Model with the two dimensions of warmth and competence to describe social groups (Fiske, Cuddy, Glick, & Xu, 2002;Fiske, Cuddy, & Glick, 2007), the model of interpersonal perception with the two dimensions love and dominance (Wiggins, Phillips, & Trapnell, 1989;Wiggins, 1979) or morality and competence (Wojciszke, Bazinska, & Jaworski, 1998;Wojciszke, 1994), and the Big Two personality concept with the dimensions communion and agency (Abele, Uchronski, Suitner, & Wojciszke, 2008;Abele & Wojciszke, 2007;Wiggins, 1991). Though these models differ in several critical aspects, one clear commonality emerges from their joint examination: There are two dimensions, namely valence (or morality/warmth/love/communion) and dominance (or competence/agency), which individuals rely on when referring to individuals, social groups, or to themselves.…”
Section: General Spontaneous Personality Judgments Based On Facesmentioning
confidence: 99%
“…Such scales were then revised and improved in psychometric terms and in terms of predictive validity (Wiggins, Phillips, & Trapnell, 1989). Accordingly, we assessed warmth versus coldness using the IAS-R (Wiggins, Trapnell, & Phillips, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Cold individuals view others as less trustworthy, whereas warm individuals view others as more trustworthy (Moskowitz, 2010). Cold individuals often seek to isolate the self from others, whereas warm individuals are, if anything, sometimes too dependent on others and motivated to please them (Strack & Lorr, 1994; Wiggins & Pincus, 1989). A communal (Bakan, 1966) label for this dimension is apt because warm individuals score higher in femininity and quite a few other motivations and traits suggestive of a greater appreciation for others and goals to accommodate to others in everyday social interactions (Locke, 2011; Markey & Markey, 2007; Wiggins & Broughton, 1991).…”
mentioning
confidence: 99%